Exploration of Ethics in the Development of Artificial Intelligence: A Literature Review on Social and Moral Implications (International Forum of Researchers and Lecturers, 2024)
This research aims to explore the ethical dimensions in the development of Artificial Intelligence (AI) with a focus on its social and moral implications. The research method involves a literature review to gain a profound understanding of the social and moral impact arising from AI development. Analysis is conducted on various literature sources, including articles, books, and AI-related ethical initiatives. The Future of Life Institute highlights the significant potential of artificial intelligence across various sectors but also underscores significant ethical challenges. This initiative requires careful understanding and handling to ensure that AI development aligns with moral and social values. Ethical issues related to unfair compensation for workers in the 'mechanical turk' industry and the impact of technology companies on human rights and democracy are identified. Furthermore, the research describes ethical issues in the use of personal data to train AI models, emphasizing individual rights regarding trained models and the protection of data subject identities. Additionally, the relationship between humans and robots raises ethical questions about their influence on human values and the potential for violent impacts. This exploration also discusses AI-related ethical initiatives emphasizing human rights, well-being, accountability, and transparency. The Ethically Aligned Design Guidelines from IEEE serve as a primary reference, emphasizing the need for AI development based on ethical principles and human rights. In conclusion, this research underscores the importance of awareness regarding the social and moral implications in AI development. Moral principles such as openness, accountability, justice, security, and freedom serve as guiding principles to ensure that AI provides positive benefits without sacrificing human values.